Molecular dynamics simulation study on the influence of graphene monolayers and laminates on the mechanical properties of graphene aluminum based composites - Shanming Fan; Qing Yu; Mingjun Peng; Hengyong Bu; Xiaolong Zhou; Jun Li; Yonghua Duan; Mengnie Li (Journal of Materials Research and Technology)
This study investigated the compressive properties of Gra/Al nanolaminated composites using molecular dynamics (MD) simulations. The results demonstrate that the thickness of graphene layers significantly influences the strength and Young's modulus of the Gra/Al composite, effectively impeding dislocation propagation. A reduction in aluminum layer thickness correlates with enhanced composite performance. Compared to pure aluminum, the graphene layers improve the composite's Young's modulus, strength, and ductility. Additionally, graphene layers intensify dislocation interactions, increasing the density of sessile dislocations (e.g., Stair-rod dislocations and Hirth dislocations), which hinder dislocation glide and thereby strengthen the composite. Temperature simulations reveal that the Gra/Al composite exhibits suppressed plastic deformation at low temperatures. However, as temperature rises, the proliferation of defects within the composite leads to a decline in both strength and modulus.